2018
DOI: 10.1111/gfs.12399
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous fungi in wrapped forages determined with different sampling and culturing methods

Abstract: The use of wrapped forage bales with high dry‐matter (DM) content implies risk of fungal growth inside the wrapping, and impaired feed quality. Since fungi may be unevenly distributed in bales, the method of sampling can influence the outcome of the analysis. Three common sampling methods for detection of fungi in wrapped forage were compared: direct plating of visible mouldy patches on bale surfaces (Method I), direct plating of pieces of foliage from drilled core samples (Method II) and quantitative analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
(35 reference statements)
3
12
0
Order By: Relevance
“…Eight species of Fusarium were found in the samples from nine farms in the current study as reported in Schenck et al, (). Fusarium species have previously been identified in Norwegian bale silage by Skaar (), as well as in Irish bale silage (O’Brien et al, ; ), although in small amounts and in a small proportion of the bales (less than 10% of sampled bales).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Eight species of Fusarium were found in the samples from nine farms in the current study as reported in Schenck et al, (). Fusarium species have previously been identified in Norwegian bale silage by Skaar (), as well as in Irish bale silage (O’Brien et al, ; ), although in small amounts and in a small proportion of the bales (less than 10% of sampled bales).…”
Section: Discussionsupporting
confidence: 78%
“…The fungal species detected varied between the methods used and are reported in detail elsewhere (Schenck et al, ). On 110 of the 124 farms, a total of 52 fungal species were identified using all three sampling and culturing methods (Schenck et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations